2012
DOI: 10.1557/mrs.2012.39
|View full text |Cite
|
Sign up to set email alerts
|

The energy–water nexus: Water use trends in sustainable energy and opportunities for materials research and development

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The analysis indicated that the cost of water would need to increase to $2.50 MW −1 to support an NGCC plant with dry cooling. The importance of assessing the cost of conserved water to evaluate different drought proofing options was also emphasized in previous studies [51].…”
Section: How Can We Enhance Resilience Of Thermoelectric Generation Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis indicated that the cost of water would need to increase to $2.50 MW −1 to support an NGCC plant with dry cooling. The importance of assessing the cost of conserved water to evaluate different drought proofing options was also emphasized in previous studies [51].…”
Section: How Can We Enhance Resilience Of Thermoelectric Generation Tmentioning
confidence: 99%
“…Several technological advances are being researched for using these non-traditional water sources for electricity generation [51]. Additional energy penalties are incurred because energy is required to treat and transport the water.…”
Section: Increasing Electric and Water Suppliesmentioning
confidence: 99%
“…17 Because of long lifespans of power plants, current power plant choices may impact water resources for decades into the future. Many studies show that different aspects of power plants, such as energy source, generator technology, or cooling system have varying water requirements.…”
Section: Introductionmentioning
confidence: 99%
“…If you are interested in further reading on sustainability, I encourage you to read the MRS Bulletin issue on "Materials for Sustainable Development" (April 2012). 32 I also suggest the special section on "Rethinking the Global Supply Chain" (Science 344, 1100 [2014]). …”
Section: Features Posterminariesmentioning
confidence: 99%